Step-by-step explanation:
The polynomial is given below as
![f(x)=x^4+2x^3-7x^2-8x+12](https://img.qammunity.org/2023/formulas/mathematics/college/ewu40pue3m1mghgsnkzr3y8tycl8i1jc2z.png)
Given in the question above the real zeros are gotten below as
![x=-3,-2,1,2](https://img.qammunity.org/2023/formulas/mathematics/college/p61vzp6no2wfhrtzs7xq7mxascqtldwklx.png)
Concept:
To figure out the factor form of the polynoimial, we will equate each zero to x below as
![\begin{gathered} x=c \\ (x-c) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1ypgsgt7d79zqlmzlwsr7gfnd0d7bbwh2e.png)
Therefore,
The factored form of the polynomial will be
![\begin{gathered} f(x)=x^(4)+2x^(3)-7x^(2)-8x+12 \\ x=-3,x=-2,x=1,x=2 \\ f(x)=(x+3)(x+2)(x-1)(x-2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hvjkm300wb1bdgulx49gy5nd6ynwguhgxw.png)
Hence,
Using the real zeros of f(x) , the factored form of the polynomial is
![\Rightarrow f(x)=(x+3)(x+2)(x-1)(x-2)](https://img.qammunity.org/2023/formulas/mathematics/college/g5965lata4cucof57go74ft4a4iyn8t64w.png)